Factors Influencing the Natural Menopause Age among Women Attending Gynaecology Outpatient Clinic at a Tertiary Care Hospital in Central India - Nirmala Kiron; Nishant Gupta; Shiwani Lilhore; Durgesh Shukla (RGUHS Journal of Nursing Sciences)
Background A woman enters the fertility period and then eventually comes a phase when her ovaries start to malfunction. It is challenging to pinpoint the exact age at which menopause begins for each woman.Objectives The present study was conducted to assess the socio demographic factors life style factors menstrual and reproductive factors among postmenopausal women and to determine the association of these factors with the menopausal age.Methods The present hospital based cross-sectional study was conducted including 330 women aged 45-65 years visiting the Obstetrics and Gynaecology Outpatient Department OPD at a teaching hospital. The interview proforma comprised questions regarding socio-demographic profile lifestyle factors menstrual and reproductive factors. Statistical tests like Chi-square test and logistic regression analysis were applied. Frequency percentage Odds ratio OR with their respective 95 confidence interval was calculated and P value lt0.05 was considered as statistically significant.Results In present study 63.03 of women attained menopause before the age of 45 years. The odds of developing early menopause le45 years among urban women were higher compared to rural women OR 3.39 95 CI 2.12-5.43. Among married women odds of developing early menopause le45 years were 4.19 times higher as compared to unmarried widowed divorcee and separated females. The odds of developing early menopause among women who attained menarche at the age of le13 years were 52 lower than those who attained menarche at gt13 years of age. The odds of developing early menopause le45 years among women with parity le 3 were 3.14 times 95 CI 1.68-5.85 higher as compared to women having parity gt5.Conclusion In this study area of residence marital status socio-economic class body mass index BMI history of addiction age at menarche age at first delivery and parity were associated with natural menopause age indicating that social lifestyle and reproductive factors may have an impact on menopausal age.